Measuring teaching effectiveness for Native American learners - Gary J. Conti (Adult Education Research Conference, 1993)
Tribal colleges offer the most hopeful opportunity for quality higher education among Native Americans. To assist in improving teaching effectiveness, an instrument is being developed based upon teaching and learning information generated from field-based interviews with tribal college students. This instrument is designed for completion by students for judging their teacher's effectiveness.